Comparison among rooting systems of Coffea arabica L. plants obtained by cuttings and seeds - Jesus, Adriana Madeira Santos; Carvalho, Samuel Pereira de; Soares, Ângela Maria (Coffee Science - ISSN 1984-3909, 2007)
Vegetative propagation or cloning of F1 hybrids represents an economy of time and resources for Coffea arabica L. breeding programs. Nevertheless, not much is known about the rooting system of coffee plants propagated by cuttings. An essay was carried out aiming to evaluate Coffea arabica rooting system of plants obtained by vegetative and seedling propagation. Cuttins of the Acaiá and Rubi cultivar with previously developed roots, about 3cm long, that have been free for 90 days of any contact with plant growth regulators were transplanted to plastic bags. At the same time, seeds from the same cultivars were planted on the same plastic bags and stored on a covered commercial nursery with 50% shading. Common cultivation methods were used during seedling development. Bioplant was used as substratum and Osmocote as fertilizer supplier. Root length and diameter were evaluated by using the computational program QUANTRAIZ. It was observed that young coffee plants originated by cuttings produced fine root system longer and heavier than the root system of plants formed by seeds. Most part of the roots developed by the seedlings, more than 98%, was composed by fine roots by which the plant is able to absorb water and mineral salts.